Genetic Deficiency of TRAF5 Promotes Adipose Tissue Inflammation and Aggravates Diet-Induced Obesity in Mice. Issue 10 (5th August 2021) - Gissler, Mark Colin; Anto-Michel, Nathaly; Pennig, Jan; Scherrer, Philipp; Li, Xiaowei; Marchini, Timoteo; Pfeiffer, Katharina; Härdtner, Carmen; Abogunloko, Tijani; Mwinyella, Timothy; Sol Mitre, Lucia; Spiga, Lisa; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: The accumulation of inflammatory leukocytes is a prerequisite of adipose tissue inflammation during cardiometabolic disease. We previously reported that a genetic deficiency of the intracellular signaling adaptor TRAF5 (TNF [tumor necrosis factor] receptor–associated factor 5) accelerates atherosclerosis in mice by increasing inflammatory cell recruitment. Here, we tested the hypothesis that an impairment of TRAF5 signaling modulates adipose tissue inflammation and its metabolic complications in a model of diet-induced obesity in mice. Approach and Results: To induce diet-induced obesity and adipose tissue inflammation, wild-type or Traf5 −/− mice consumed a high-fat diet for 18 weeks. Traf5 −/− mice showed an increased weight gain, impaired insulin tolerance, and increased fasting blood glucose. Weight of livers and peripheral fat pads was increased in Traf5 −/− mice, whereas lean tissue weight and growth were not affected. Flow cytometry of the stromal vascular fraction of visceral adipose tissue from Traf5 −/− mice revealed an increase in cytotoxic T cells, CD11c + macrophages, and increased gene expression of proinflammatory cytokines and chemokines. At the level of cell types, expression of TNFα, MIP (macrophage inflammatory protein)-1α, MCP (monocyte chemoattractant protein)-1, and RANTES (regulated on activation, normal T-cell expressed and secreted) was significantly upregulated in Traf5 -deficient adipocytes but not in Traf5 -deficient leukocytes from visceral adipose tissue. Finally, Traf5 expression was lower in adipocytes from obese patients and mice and recovered in adipose tissue of obese patients one year after bariatric surgery. Conclusions: We show that a genetic deficiency of TRAF5 in mice aggravates diet-induced obesity and its metabolic derangements by a proinflammatory response in adipocytes. Our data indicate that TRAF5 may promote anti-inflammatory and obesity-preventing signaling events in adipose tissue.